2008
DOI: 10.1017/s0007114508047727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with the green tea polyphenol epigallocatechin-3-gallate on insulin resistance and associated metabolic risk factors: randomized controlled trial

Abstract: Animal evidence indicates that green tea may modulate insulin sensitivity, with epigallocatechin-3-gallate (EGCG) proposed as a likely healthpromoting component. The purpose of this study was to investigate the effect of dietary supplementation with EGCG on insulin resistance and associated metabolic risk factors in man. Overweight or obese male subjects, aged 40-65 years, were randomly assigned to take 400 mg capsules of EGCG (n 46) or the placebo lactose (n 42), twice daily for 8 weeks. Oral glucose toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(200 citation statements)
references
References 56 publications
9
182
0
3
Order By: Relevance
“…The third trial was carried out in 88 overweight or obese male subjects [55]. The participants were randomly assigned into two groups, treatment and control.…”
Section: Green Teamentioning
confidence: 99%
“…The third trial was carried out in 88 overweight or obese male subjects [55]. The participants were randomly assigned into two groups, treatment and control.…”
Section: Green Teamentioning
confidence: 99%
“…Hypotensive effects have also been observed in other trials [9,13,14,44], with the suggested mechanism of action being vasodilation in response to the stimulation and amplified production of nitric oxide by the vascular endothelium. This is in agreement with the data from a study in an animal model, the stroke-prone, spontaneously hypertensive rats, in which GTCs were shown to significantly lower SBP and DBP [45].…”
Section: Discussionmentioning
confidence: 82%
“…For the FA oxidation assay, the growth medium was removed, and the cell monolayers were washed three times with PBS. Next, HepG2 cells were lipid-loaded with DMEM containing 1.75 mM [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]palmitate (57 mCi/mM; Perkin Elmer) conjugated to 1 mg/ml FA-free BSA for 18 h. The medium was removed and centrifuged to remove cellular debris. It was then placed in a sealed container with a reservoir containing 0.5 ml of 1 M NaOH.…”
Section: Fa Oxidationmentioning
confidence: 99%